Analisis Inovasi Teknologi dan Sistem Keamanan Terhadap Kepercayaan Nasabah dengan Kepuasan Nasabah Sebagai Variabel Intervening - Izzati, Salsabilla; Purnamasari, Femei; Fitri, Anggun Okta (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study is motivated by the importance of technological innovation and security systems in enhancing customer trust in Islamic mobile banking services. The objective of this study is to analyze the effects of technological innovation and security systems on customer trust, with customer satisfaction serving as a mediating variable among Islamic mobile banking users in Bandar Lampung City. This study employed a quantitative approach using an associative research method. The sample consisted of 100 respondents selected through purposive sampling. Data were collected using a questionnaire and analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4.0 software. The findings indicate that technological innovation has a significant positive effect on both customer trust and customer satisfaction. Meanwhile, security systems have a significant positive effect on customer trust but do not have a significant effect on customer satisfaction. Customer satisfaction is also found to have a significant positive effect on customer trust. Furthermore, customer satisfaction does not mediate the relationship between technological innovation and customer trust, but it does mediate the relationship between security systems and customer trust. Based on these findings, it can be concluded that improving customer trust in Islamic mobile banking services requires continuous technological innovation, stronger security systems, and enhanced customer satisfaction.